2022
DOI: 10.1093/molbev/msac074
|View full text |Cite
|
Sign up to set email alerts
|

Global Patterns of Subgenome Evolution in Organelle-Targeted Genes of Six Allotetraploid Angiosperms

Abstract: Whole-genome duplications (WGDs) are a prominent process of diversification in eukaryotes. The genetic and evolutionary forces that WGD imposes upon cytoplasmic genomes are not well understood, despite the central role that cytonuclear interactions play in eukaryotic function and fitness. Cellular respiration and photosynthesis depend upon successful interaction between the 3000+ nuclear-encoded proteins destined for the mitochondria or plastids and the gene products of cytoplasmic genomes in multi-subunit com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 298 publications
(389 reference statements)
1
29
0
Order By: Relevance
“…Polyploidy results in duplicated genes that play important roles in crop domestication and disease resistance ( Renny-Byfield and Wendel, 2014 ). A recent subgenome evolution analysis of allotetraploid angiosperms revealed that subgenomes of the allotetraploids exhibit unequal rates of protein evolution, showing separate evolutionary trajectories ( Sharbrough et al, 2022 ). Consistently, N. benthamiana obtained two EIX-responding loci with diverged functions from different ancestors.…”
Section: Discussionmentioning
confidence: 99%
“…Polyploidy results in duplicated genes that play important roles in crop domestication and disease resistance ( Renny-Byfield and Wendel, 2014 ). A recent subgenome evolution analysis of allotetraploid angiosperms revealed that subgenomes of the allotetraploids exhibit unequal rates of protein evolution, showing separate evolutionary trajectories ( Sharbrough et al, 2022 ). Consistently, N. benthamiana obtained two EIX-responding loci with diverged functions from different ancestors.…”
Section: Discussionmentioning
confidence: 99%
“…We followed the methods of Sharbrough et al (2022) to identify orthologous genes arising from allopolyploidy (i.e. “quartets” consisting of one homolog from each diploid parent and 2 homoeologs from the allopolyploid).…”
Section: Methodsmentioning
confidence: 99%
“…We retained orthogroups containing 3 or more homologs, extracted coding sequences (CDS) for those proteins, and aligned each using the L-INS-i algorithm in MAFFT (v7.480) ( Katoh and Standley 2013 ). Model selection was done using jModelTest2 v2.1.10 ( Darriba et al 2012 ) and phylogenetic inference was performed in PhyML v3.3.20211021 ( Guindon and Gascuel 2003 ), as described previously ( Sharbrough et al 2022 ). Because these gene trees often contain multiple orthologous groups resulting from ancient duplications, we extracted subtrees containing potential quartets (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…1a), suggesting VDL was a tetraploid species, which may be more challenging for genome sequencing and assembly. A recent study reported that subgenome sequence divergence (measured in synonymous substitutions per synonymous site, Ks) since allopolyploidization of six allopolyploid angiosperms ranged from 0.026 to 0.105 [26], while sequence divergence between allelic chromosomes of autotetraploid alfalfa is much lower, peaked at ~ 0.01 [27]. We applied the WGDI pipeline (whole-genome duplication identification v0.4.7 [28]) to perform collinearity analysis of the The phylogenetic tree is consistent with the tree constructed by Pellicer, et al [25], and VDL is located in "2n = 4x = 32" clade, suggesting tetraploid.…”
Section: High Proportions Of Ucr Are Common For Polyploid Genomes Ass...mentioning
confidence: 99%